Model Pembelajaran PAI Berbasis Project-Based Learning dan Pendekatan Kolaboratif dalam Membentuk Akhlak Mulia Peserta Didik di SD Negeri Besuk Kidul, Kecamatan Besuk - Avidatul Umaidah; Ainur Rofiq Sofa (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study examines the implementation of an Islamic Religious Education (PAI) learning model based on Project-Based Learning (PjBL) and collaborative approaches in shaping students’ noble character at SD Negeri Besuk Kidul, Besuk District. The study is grounded in the research gap that PAI learning in elementary schools is often still dominated by conventional, teacher-centered methods that emphasize cognitive achievement while providing limited space for the internalization of moral values through authentic learning experiences. This research aims to analyze how PjBL and collaborative learning are designed and implemented in PAI instruction and to explore their contribution to students’ character development. A qualitative approach with a descriptive case study design was employed. The research subjects included the school principal, a PAI teacher, and elementary school students. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive data analysis model. The findings reveal that the integration of project-based and collaborative learning in PAI instruction enhances students’ noble character, particularly in terms of honesty, discipline, responsibility, cooperation, respect, and social awareness. Students actively engage in learning activities, apply Islamic values in real-life contexts, and demonstrate positive behavioral changes both in and outside the classroom. These results indicate that Project-Based Learning and collaborative approaches constitute an effective and meaningful strategy for strengthening character education in PAI at the elementary school level.